Pemanfaatan Limbah Kaleng Biskuit Untuk Pembuatan Aksesoris Pilis Pengantin Semarangan - Kuswidyaningrum NJ4; Cintya Nabilah Mulida; Nurulisma Saputri; Agus Susanti (Garina, 2023)
Semarangan bridal pilis accessories are hard to find and are not sold on the market. However, only a few people have these pilis accessories. Using biscuit tin waste can save costs and can be used as a substitute material for developing accessories. The author innovates by recycling waste biscuit tins into Semarangan bridal pilis accessories. The aim of this research is to find out how to make and use Semarangan bridal pilis accessories from waste biscuit tins, as well as to find out the results of public tests of public interest in using biscuit can waste to make Semarangan bridal pilis accessories. In this research, the author used data collection methods in the form of observation, experimentation, documentation, literature, interviews and questionnaires. The manufacturing of the Semarangan bridal accessories is carried out by three stages, namely the preparation stage of equipment and ingredients, the stage of making and the using of the accessories from the tin waste. The three expert validators choose three outcome products because they correspond to the originality of the Semarangan bridal accessories. The research's public study involved 30 respondents with respondents stated 100% to questions 1, questions 3, questions 5, question 6 questions, and questions 8. The cutting process of the biscuits tins for bridal gold accessories ought to be reduced to make it look neater, whereas the f6000 is used as a glue